Material Development as the Dominant Students Research Topic of the Arabic Language Education at the Doctoral Programme - Abdul Wahab Rosyidi; Risna Rianti Sari; Faisal Mahmoud Adam; Ahmad Fathoni (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2023)
The aim of this study was to classify the results of the dissertation, describe the research method, and present the final findings. The research method used descriptive analysis with the main dissertation data for 2012–2022, using the Milles and Huberman model analysis technique. The research result was that the focus of the dissertation study spread to ulum al-lughah and maharah al-lughah; however, it swelled to the development of teaching materials. The dissertation was written using qualitative and quantitative research models, with the type of R&D development model adapted by Borg and Gall as the majority. The final dissertation formulation looked at the characteristics of the teaching materials in each approach, theory, and frame used. For the feasibility of teaching material products at a feasible level and effectively improving language skills and knowledge. From the results of the assessment, there was no expert validation, which showed low results, and the effectiveness test failed.